2022
DOI: 10.20944/preprints202212.0222.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Entity of Cerebellar Mutism Syndrome: A Narrative Review Centered on the Etiology, Diagnostics, Prevention, and Therapeutic Options

Abstract: Cerebellar mutism syndrome (CMS), also known as posterior fossa syndrome, is encountered in a subset of children who have undergone an operative procedure of the posterior cranial fossa, mainly involving the vermis, and the most frequent underlying pathology is proved to be medulloblastoma. The most common characteristics of this syndrome include an often transient, although protracted, language impairment, emotional lability, along with cerebellar, and brainstem dysfunction. Nevertheless, a significant number… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…This discrepancy can be partially explained by two factors: first, the telovelar approach requires greater technical skill, and is therefore practiced by experienced surgeons; and second, the transvermian approach is preferred in the presence of large tumors, a well-established risk factor, introducing an additional bias. In fact, in another prospective study, surgery in a low-volume surgery center were found to increase the likelihood of CMS [5,8,10].…”
Section: Preoperative Riskmentioning
confidence: 96%
See 4 more Smart Citations
“…This discrepancy can be partially explained by two factors: first, the telovelar approach requires greater technical skill, and is therefore practiced by experienced surgeons; and second, the transvermian approach is preferred in the presence of large tumors, a well-established risk factor, introducing an additional bias. In fact, in another prospective study, surgery in a low-volume surgery center were found to increase the likelihood of CMS [5,8,10].…”
Section: Preoperative Riskmentioning
confidence: 96%
“…Preoperative language impairment has also been implicated. More precisely, 28.5% of children suffering from preoperative language impairment and developed cerebellar mutism postoperatively [10].…”
Section: Preoperative Riskmentioning
confidence: 99%
See 3 more Smart Citations